Diskusi Interaktif Menggunakan Audiovisual untuk Meningkatkan Pengetahuan dan Sikap Remaja terhadap Perilaku Tidak Merokok - Suharto Suharto; Ronald Tolkhah; Mundhofar Mundhofar (Jurnal LINK, 2015)
This research is aimed to improve the knowledge and behavior of teenagers against smoking by using interactive discussion with audiovisual. This study uses a quasi-experimental design with pre-test and post-test with control design with a sample of 94 students that are divided into 2 groups. The experimental group consists of 54 students and 40 students belong to control group. The result shows that the treatment group or the control group increased knowledge and attitudes against smoking. In the treatment group, the change of the frequency of respondents who quit smoking is higher than in the control group. There is an increase in knowledge and attitudes of respondents to smoking behavior after an interactive discussion, so that it can be used as an alternative method to improve the knowledge, attitudes and behaviors in students.